A comparison of functional academic and daily living skills in males with fragile X syndrome with and without autism. (July 2018) - Raspa, Melissa; Franco, Vitor; Bishop, Ellen; Wheeler, Anne C.; Wylie, Amanda; Bailey, Donald B.
Highlights: Males with FXS master a variety of functional academic and daily living skills in early childhood and continue to show gains through adolscence. Foundational skills, such as counting to 10, were easier to master than more complex skills, such as knowing the value of coins and small bills. Many adult males showed independent daily living skills related to hygiene, preparing simple meals, and basic housekeeping skills. There are clear differences for most functional academic and daily living skills by autism status and number of co-occurring conditions. Both functional academic skills and daily living skills were associated with higher likelihood of community employment and independent living. Abstract: Background: Adaptive behaviors, such as functional academic and daily living skills, are critical for independence in adults with intellectual and developmental disabilities. However, little is known about these skills in fragile X syndrome (FXS), the most common form of inherited intellectual disability. Aims: The purposes of this study were to describe the functional academic and daily living skills of males diagnosed with FXS across different age groups and compare skill attainment by autism status and other common co-occurring conditions. Methods and procedures: We used survey methods to assess parent-reported functional academic and daily living skills in 534 males with FXS. Functional academic skills included time and schedules, money, math, reading, and writing skills. Daily living skills included hygiene, cooking, laundry and housekeeping, transportation, and safety skills. Outcomes and results: Analyses examined functional academic and daily living skills in a cross-sectional sample of males between ages 5 and 67. Differences in skill attainment were found by child age, co-morbid autism status, total number of co-occurring conditions, and respondent education. Functional academic and daily living skills were predictive of community employment and independent living. Conclusions and implications: These data provide important information on the mastery of both foundational and more complex adaptive skills in males with FXS. Both functional academic and daily living skills were predictive of measures of independence above and beyond other child and family characteristics. These findings point to the need to focus interventions to support the attainment of independence in males with FXS.